2012
DOI: 10.2478/v10014-012-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCl treatments on growth and biochemical parameters of castor bean (Ricinus communis L.)

Abstract: Castor bean (Ricinus communis L.) is widely cultivated throughout the world for use as a medicinal plant and oil consumption purposes; however its salt tolerance has not been clarified. To investigate the effect of salt stress on its growth and on activity of antioxidative enzymes in different organs, castor bean plants at the 4-leaf stage were subjected to 50, 100 and 200 mM NaCl admixed to Hoagland's solution for 10 days under greenhouse conditions. The results showed that salt stress inhibited plant growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…This finding was partially in agreement with our previous study in which the salinity level of 3.6 dS m −1 significantly increased taproot length, average root length, the weight of root, stem, and the whole plant (Zhou et al, 2010). But different results were reported by Janmohammadi et al (2012), who found that 50 mM NaCl resulted in a significant decrease in the root weight and leaf of castor bean seedlings. The differences between the study of Janmohammadi et al (2012) and ours probably lie in the differences in genetic background of castor seeds and the treatment method of salt.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This finding was partially in agreement with our previous study in which the salinity level of 3.6 dS m −1 significantly increased taproot length, average root length, the weight of root, stem, and the whole plant (Zhou et al, 2010). But different results were reported by Janmohammadi et al (2012), who found that 50 mM NaCl resulted in a significant decrease in the root weight and leaf of castor bean seedlings. The differences between the study of Janmohammadi et al (2012) and ours probably lie in the differences in genetic background of castor seeds and the treatment method of salt.…”
Section: Discussionmentioning
confidence: 64%
“…The activity SOD and CAT was determined following the method of Janmohammadi et al (2012). The activity of POD was assayed according to the method of Xu and Ye (1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane lipid peroxidation results in malondialdehyde (MDA) accumulation, which is an indication of membrane damage at the cellular level under salt stress (Weisamy et al, 2012). Peroxidation of membrane lipids occurs due to reactive oxygen species or lipooxygenases (Janmohammadi et al, 2012). In the present investigation, salinity stress increased oxidative stress in both wheat cultivars but to a greater degree in salt-sensitive cv.…”
Section: Discussionmentioning
confidence: 64%
“…Several studies have considered the accumulation of biomass as an essential index to estimate the level of plant's tolerance to abiotic stresses (Hajlaoui et al, 2010;Janmohammadi et al, 2012;Zörb et al, 2013). In concordance with, sunflower genotypes displayed differential biomass accumulation as affected by salt stress.…”
Section: Resultsmentioning
confidence: 90%